Video Animasi 3 Dimensi terhadap Kemampuan Mengenal Angka 1-10 pada Siswa Kesulitan Belajar - Lela, Adinda Candra; Prystiananta, Nostalgianti Citra; Sukmawati, Bhennita (JOEAI (Journal of Education and Instruction), 2025)
This study aims to determine the effect of using 3-dimensional animated video media on students' ability to recognize numbers 1-10, particularly those with learning difficulties, at Muhammadiyah 1 Elementary School in Jember. The method employed is Single Subject Research (SSR) with an A-B research design, comprising 15 meeting sessions: 5 baseline sessions and 10 intervention sessions. During the baseline session, the percentage of scores was 45%, 47.5%, 45%, 45%, and the intervention percentage was 52.5%, 55%, 57.5%, 65%, 65%, 70%, 70%, 67.5%, 75%, 75%. According to the results of the baseline study, the lowest score was 45%, and the highest score was 47.5%. During the intervention session, the lowest score was 52.5%, and the highest score in the final session was 75%. The level change in the second stage was +7.5 %. In conclusion, the use of 3D animated video media has an impact on the ability to recognize numbers 1–10 in students with learning difficulties at Muhammadiyah 1 Elementary School in Jember.   Keywords: A-B Design, Learning Difficulties, Number Recognition, Single Subject Research, Animated Video